Fundamental characteristics in power generation by heat engines on ocean thermal energy conversion (Construction of finite-time thermodynamic model and effect of heat source flow rate) - Takeshi YASUNAGA; Yasuyuki IKEGAMI (Nihon Kikai Gakkai ronbunshu, 2020)
Ocean thermal energy conversion (OTEC) is a system to convert the thermal energy stored as the vertical temperature gradient in the ocean into the electricity. The authors have proposed a theoretical thermodynamic model using a reversible heat engine to calculate the available thermal energy, exergy, normalized thermal efficiency and exergy efficiency in OTEC based on finite-time thermodynamics. In an OTEC system, the available power will be a balance of the performance of component, such as heat exchangers, turbine/generator, pumps and a working fluid. Thus, the performance of each component has a significant effect on net power production as the efficiency of heat engines driven by low temperature difference is theoretically low. This research develops the conventional OTEC theoretical model, and to calculate the theoretical net power of OTEC considering irreversibility in the heat engine, heat exchange process and fluid flow of heat sources using a coefficient of irreversibility in the heat engine and the effectiveness of heat transfer to apply optimum operation or design optima. The theoretical performance calculated by the model compared with the 30 kW OTEC experimental results in two cases of configurations with different types of plate heat exchangers and units. Consequently, the performance of the thermodynamic model and the experimental results show good agreement using the experimental heat exchanger performance and the irreversibility of heat engine in the thermodynamic model, therefore, the results verified the effectiveness of the novel model.